Pengembangan Metode Pembelajaran Interaktif Berbasis Adobe Ilustrator Dalam Pembuatan Desain Poster Pada SMK Telkom Medan - Aulia, Hasypa; Manurung, Liza Alzahra; Raihan, Muhammad Syafiq; Akila, Gadiel Naufa; Ikhwan, Ali (CV. Information Technology Training Center - Indonesia (ITTC), 2023)
Education is self-development work related to the development of skills, intelligence, character, creativity and soft skills of the younger generation. Multimedia-based learning media can be used to increase students' understanding of using Adobe Illustrator. Half of the members of class 10-4 TKJ Telkom Medan have a high interest in the subject of poster design or Adobe illustrator[1]. But they are not proficient in using the features in Adobe Illustrator in making posters. So that this research aims to introduce the features in Adobe Illustrator and their functions to students so that they know about making calligraphy through the Adobe Illustrator application. Utilization of the Adobe Illustrator application program can improve student soft skills and creativity. So they can pose as they want